Paclitaxel effects on axonal localization and vesicular trafficking of NaV1.8 - Baker, Christopher A.; Tyagi, Sidharth; Higerd-Rusli, Grant P.; Liu, Shujun; Zhao, Peng; Dib-Hajj, Fadia B.; Waxman, Stephen G.; Dib-Hajj, Sulayman D. (Frontiers in Molecular Neuroscience, 2023)
Patients treated with paclitaxel (PTX) or other antineoplastic agents can experience chemotherapy-induced peripheral neuropathy (CIPN), a debilitating side effect characterized by numbness and pain. PTX interferes with microtubule-based transport, which inhibits tumor growth via cell cycle arrest but can also affect other cellular functions including trafficking of ion channels critical to transduction of stimuli by sensory neurons of the dorsal root ganglia (DRG). We examined the effects of PTX on voltage-gated sodium channel NaV1.8, which is preferentially expressed in DRG neurons, using a microfluidic chamber culture system and chemigenetic labeling to observe anterograde channel transport to the endings of DRG axons in real time. PTX treatment increased the numbers of NaV1.8-containing vesicles traversing the axons. Vesicles in PTX-treated cells exhibited greater average velocity, along with shorter and less frequent pauses along their trajectories. These events were paralleled by greater surface accumulation of NaV1.8 channels at the distal ends of DRG axons. These results were consistent with observations that NaV1.8 is trafficked in the same vesicles containing NaV1.7 channels, which are also involved in pain syndromes in humans and are similarly affected by PTX treatment. However, unlike Nav1.7, we did not detect increased Nav1.8 current density measured at the neuronal soma, suggesting a differential effect of PTX on trafficking of Nav1.8 in soma versus axonal compartments. Therapeutic targeting of axonal vesicular traffic would affect both Nav1.7 and Nav1.8 channels and increase the possibilities of alleviating pain associated with CIPN.